Pengembangan Media Video Pembelajaran Pola Gerak Shooting Sepakbola Pada Santri Kelas VII MTS Unggulan PP. Amanatul Ummah Pacet - Annas, Amsal; Widodo, Achmad; Tuasikal, Abdul Rachman Syam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The background in this study is the lack of development of the learning process for big ball games, especially soccer games in Mts Unggulan Pondok Pesantren Ammanatul Ummah. The problem in this research is how to develop a soccer learning model through video media learning shooting motion patterns in class VII students of MTs Unggulan PP. Amanatul Ummah Pacet? The purpose of this research is to produce a model of shooting motion patterns in soccer learning. The method used in this research is research and development (Research and Development) from Borg and Gall. The development of shooting motion patterns is adapted to the theme of physical education, sports and health during one year of learning. The product was validated by physical education experts in the field of soccer, experts in the analysis of motion learning modifications in soccer games and PJOK teachers in the field of soccer. The product trials consisted of trials I and trials II at the superior MTs of the Ammanatul Ummah Islamic Boarding School. Based on the results of validation from experts in physical education in the field of football, the results were 86.6%, while the validation results were from experts on the analysis of modifications to learning motion in soccer games, which showed results of 96%, and experts from PJOK teachers in the field of football, showed results of 94.6%. So, based on the experts, the results of research on developing video media for learning shooting motion patterns in class VII MTs students are feasible to use.